2015
DOI: 10.1371/journal.pone.0144954
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Red Propolis Attenuates Inflammatory Signaling Cascade in LPS-Activated Macrophages

Abstract: Although previous studies suggested an anti-inflammatory property of Brazilian red propolis (BRP), the mechanisms involved in the anti-inflammatory effects of BRP and its activity on macrophages were still not elucidated. This study aimed to evaluate whether BRP attenuates the inflammatory effect of LPS on macrophages and to investigate its underlying mechanisms. BRP was added to RAW 264.7 murine macrophages after activation with LPS. NO production, cell viability, cytokines profile were evaluated. Activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…After treatment with BP, the expression levels of inflammatory cytokines were significantly downregulated. Previous studies also showed that propolis attenuates the expression of pro‐inflammatory cytokines in different cell types, which is consistent with the current findings. Pro‐inflammatory cytokine expression levels were higher in the HBSS group than in the BP group, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…After treatment with BP, the expression levels of inflammatory cytokines were significantly downregulated. Previous studies also showed that propolis attenuates the expression of pro‐inflammatory cytokines in different cell types, which is consistent with the current findings. Pro‐inflammatory cytokine expression levels were higher in the HBSS group than in the BP group, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…In rat NP cells, CCAAT/enhancer binding protein β (C/EBPβ) increases the levels of TNF-α, which is mediated by the extracellular signalregulated kinase 1/2 (ERK1/2) and p38 mitogen activated protein kinase (MAPK) pathways [19]. In monocytes and macrophages, lipopolysaccharide (LPS) induces TNF-α expression by activating early growth response factor-1 (Egr-1) [20], activator protein-1 (AP-1) [21], MAPK [22], and nuclear factor-κB (NF-κB) [23]. In neonatal rat cardiac fibroblasts, the activating transcription factor-2 (ATF-2)/c-Jun signaling pathway, but not NF-κB, is required for the up-regulation of TNF-α expression induced by angiotensin II and LPS [24].…”
Section: Structure and Synthesis Of Tnf-αmentioning
confidence: 99%
“…In contrast to European propolis, rich in flavonoids, Brazilian propolis is characterized by the presence of derivatives of prenylated cinnamic acid [8,9]. Brazilian propolis has become popular as a healthy dietary supplement, and a number of innovative propolis-containing foods and beverages have been developed, because it has been proven to prevent inflammation, heart diseases, diabetes, and cancer [10,11]. Moreover, Brazilian certified organic propolis (OP), produced in environmental conservation and reforestation areas in the states of Paraná and Santa Catarina, has attracted the attention of Europeans due to its mild flavor and absence of heavy metals and pesticides.…”
Section: Introductionmentioning
confidence: 99%